Identification of blaESBL- and blaCARBA- Positive Multi-Drug Resistant Mixta calida Isolates from Distinct Human Hosts - Francesca McDonagh; Kate Ryan; Aneta Kovářová; Anna Tumeo; Christina Clarke; Martin Cormican; Georgios Miliotis (International Journal of Medical Microbiology)
Objective: This study aimed to investigate the identification of blaCARBA-positive multidrug-resistant Mixta calida isolates from human hosts and to elucidate their genomic determinants in a species-wide context. Methods: Two carbapenemase-producing M. calida isolates were received by the Galway Reference Laboratory Service in Ireland between June and July 2024. One isolate originated from a sputum sample, while the other was recovered from a routine screening rectal swab. Initial identification was performed using MALDI-ToF mass spectrometry, with genomic confirmation via 16S rRNA sequencing, digital DNA-DNA hybridization, and Average Nucleotide Identity analysis. Antimicrobial susceptibility testing was conducted using a MicroScan panel, following EUCAST and CLSI guidelines. Whole-genome sequencing, plasmid replicon typing, and antibiotic-resistance-gene and virulence-factor profiling were employed. Comparative analysis included all additional canonical M. calida genomes from NCBI database. Results: Both Irish isolates were taxonomically placed as M. calida and exhibited multidrug resistance against penicillins, cephalosporins, monobactams and ertapenem. The acquired genes blaKPC-3, blaOXA-9, and blaTEM-122 were detected on plasmid-borne contigs, indicating horizontal acquisition. Seven plasmid replicon types were shared between the two isolates. Both plasmid replicons and acquired antimicrobial-resistance-genes (ARGs) were seldomly identified across the species. Phylogenetic inference based on core genome analysis identified a monophyletic cluster, suggesting a single introductory event. Conclusion: This study documents a dual occurrence of blaCARBA-positive M. calida in human colonisation and infection. The findings highlight the potential for horizontal-gene-transfer to drive the emergence of multidrug-resistant profiles in the species, underscoring the need for enhanced surveillance, diagnostic precision, and targeted infection control strategies to mitigate public health risks. Impact statement: This study reports blaESBL and blaCARBA-positive multi-drug resistant Mixta calida isolates from distinct human hosts. Genomic analysis revealed the co-occurrence of plasmid-borne resistance genes blaKPC-3, blaOXA-9, and blaTEM-122. Species-wide phylogenetic analysis grouped the two isolates into a monophyletic cluster, suggesting a single introductory event.